2022
DOI: 10.1021/acs.jproteome.2c00449
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Amino Acid, Lipid, and Acylpyruvate Metabolism in Idiopathic Intracranial Hypertension: A Non-targeted Case Control and Longitudinal Metabolomic Study

Abstract: Background : Idiopathic intracranial hypertension (IIH) is characterized by increased intracranial pressure occurring predominantly in women with obesity. The pathogenesis is not understood. We have applied untargeted metabolomic analysis using ultrahigh-performance liquid chromatography–mass spectrometry to characterize the cerebrospinal fluid (CSF) and serum in IIH compared to control subjects. Methods and findings : Samples were collected from IIH patients ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“… 190 Individuals with IIH have an abnormal metabolome, unique androgen signature, and dysregulated glucocorticoid phenotype. 113 , 191 Growing evidence suggests that IIH may not be purely idiopathic but is related to systemic metabolic and hormonal disturbances. The early diagnosis and treatment of IIH still pose challenges.…”
Section: Discussionmentioning
confidence: 99%
“… 190 Individuals with IIH have an abnormal metabolome, unique androgen signature, and dysregulated glucocorticoid phenotype. 113 , 191 Growing evidence suggests that IIH may not be purely idiopathic but is related to systemic metabolic and hormonal disturbances. The early diagnosis and treatment of IIH still pose challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Several exploratory untargeted metabolomic studies, involving female patients with active IIH:WT study showed dysregulation of amino acid and lipid metabolism in CSF and serum samples. Mechanistically how this relates to IIH is uncertain [25]. A similar study by the same group employed nuclear magnetic resonance spectroscopy demonstrating lower urea, raised lactate:pyruvate ratio and acetate levels in the CSF at baseline.…”
Section: Cause and Pathophysiologymentioning
confidence: 99%